2014
DOI: 10.1103/physrevlett.112.094302
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropic Blistering Instability of Highly Ellipsoidal Shells

Abstract: The formation of localized periodic structures in the deformation of elastic shells is well documented and is a familiar first stage in the crushing of a spherical shell such as a ping-pong ball. While spherical shells manifest such periodic structures as polygons, we present a new instability that is observed in the indentation of a highly ellipsoidal shell by a horizontal plate. Above a critical indentation depth, the plate loses contact with the shell in a series of well-defined "blisters" along the long ax… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 24 publications
2
11
0
Order By: Relevance
“…However, while close to threshold (i.e.δ = O(1)), previous ABAQUS simulations [7] confirm the τ dependence predicted by (17), the predicted evolution of m with increasingδ has not been observed. This shortcoming is consistent with recent work, which showed significant hurdles in numerically predicting the wrinkle number [31].…”
Section: Comparison Of Floating Films To Pressurized Shellsmentioning
confidence: 70%
“…However, while close to threshold (i.e.δ = O(1)), previous ABAQUS simulations [7] confirm the τ dependence predicted by (17), the predicted evolution of m with increasingδ has not been observed. This shortcoming is consistent with recent work, which showed significant hurdles in numerically predicting the wrinkle number [31].…”
Section: Comparison Of Floating Films To Pressurized Shellsmentioning
confidence: 70%
“…with κ the turbulent diffusivity of αm. Exploring the influence of other potentially important contributions to the helicity flux (Vishniac & Cho 2001;Sur et al 2007;Vishniac 2012;Vishniac & Shapovalov 2014;Ebrahimi & Bhattacharjee 2014) is left for future work. We do, however, compare our results with results using the simple algebraic α-quenching formalism,…”
Section: Mean-field Dynamo Theorymentioning
confidence: 99%
“…Below, we discuss some terms in Equation (6) that have been identified and found to be significant in numerical simulations and we leave the investigation of the remaining terms in Equations (5) and (6) for future studies aided by numerical simulations. The relative contribution from each term in Equation (6) to the small-scale magnetic helicity transport equation has been explored recently through numerical simulations (Ebrahimi & Bhattacharjee 2014;Vishniac & Shapovalov 2014). Vishniac & Shapovalov (2014) found that the advective flux, (a · b)U, is the most dominant term in Equation (6), contributing about 80% of the helicity flux.…”
Section: Nonlinear Mean-field Dynamo and Magnetic Helicity Dynamicsmentioning
confidence: 99%